2016
DOI: 10.1039/c6ra10199b
|View full text |Cite
|
Sign up to set email alerts
|

Benzocyclohexane oxide derivatives and neolignans from Piper betle inhibit efflux-related resistance in Staphylococcus aureus

Abstract: This research seeks to address the problem of methicillin-resistant Staphylococcus aureus (MRSA) by discovering synergistic antibacterial natural substances from traditional Chinese herbs using antibacterial bioassays. Six compounds, including three neolignans (À)-acuminatin (1), (À)-denudatin B (2), puberulin D (3), and three benzocyclohexane oxide derivatives ferrudiol (4), ellipeiopsol B (5) and zeylenol (6), were isolated and purified by silica gel and reverse-phase silica gel column chromatography, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Oluwatuyi et al (2004) demonstrated that the abietane diterpenes, carnosic acid and carnosol, which were isolated from Rosmarinus officinalis , had modest EPI activity. Carnosic acid decreased the MIC values of erythromycin against RN4220 (pUL5054; msrA ++) by eightfold and caused a twofold decreased in the EtBr MIC against the SA-1199B strain of S. aureus , which overexpresses the norA gene that encodes the NorA MDR efflux pump (Sun et al, 2016), and that of tetracycline against the XU212 strain of S. aureus , which possesses the TetK tetracycline efflux protein (Sun et al, 2016). However, carnosic acid inhibited EtBr efflux in SA-1199B cells, suggesting that it has weak NorA-inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Oluwatuyi et al (2004) demonstrated that the abietane diterpenes, carnosic acid and carnosol, which were isolated from Rosmarinus officinalis , had modest EPI activity. Carnosic acid decreased the MIC values of erythromycin against RN4220 (pUL5054; msrA ++) by eightfold and caused a twofold decreased in the EtBr MIC against the SA-1199B strain of S. aureus , which overexpresses the norA gene that encodes the NorA MDR efflux pump (Sun et al, 2016), and that of tetracycline against the XU212 strain of S. aureus , which possesses the TetK tetracycline efflux protein (Sun et al, 2016). However, carnosic acid inhibited EtBr efflux in SA-1199B cells, suggesting that it has weak NorA-inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, neolignans from P. betle were revealed having potent synergistic activity in antibacterial assays against the drug-resistant S. aureus strain SA1199B 10 . In this research, all compounds isolated from P. betle were guided by synergistic antimicrobial screening against SA1199B, but none showed direct inhibitory activity at a concentration of 256 µg/mL.…”
Section: Synergistic Antibacterial Activitiesmentioning
confidence: 98%
“…[ 5 6 7 ] These compounds have been reported as antibacterial agents against pathogens. [ 8 9 ] Myristica fragrans Houtt. is an important plant source of neolignans used for preventing cancer and leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%